Wind-induced response of light and slender arched structures in twin arrangement: Wind tunnel tests and full-scale monitoring. (1st July 2019) - Muggiasca, Sara; Bayati, Ilmas; Giappino, Stefano; Rosa, Lorenzo; Belloli, Marco
Highlights: Wind tunnel and full-scale measurements performed on two arches in twin arrangement. Wind tunnel tests on an aeroelastic model to check possible critical behaviour. The real structure was characterized through a modal parameters identification. Continuous monitoring of the structure was performed. Abstract: The paper presents the complete activity carried out on two light and slender arched structures in twin arrangement: the two arches built for Expo 2015 in Milan. In particular, this study represents a rare occasion of comprehensive measurements of different types and scales on the same structure: this highlights the relevance of a structured and comprehensive approach, from wind tunnel to full-scale testing, as a valuable support to design, construction and maintenance of wind-sensitive constructions. These two structures were considered potentially critical, from an aerodynamic point of view, due to their rectangular cross-wind section, that can be prone to instability and VIV problems, and to their low frequencies and structural damping that can be easily excited by the wind. Wind tunnel tests performed at Politecnico di Milano wind tunnel, on aeroelastic models of the two arches confirmed the occurrence of galloping dynamic instability at wind speeds lower than the design value and gave indication concerning the required structural damping to control the phenomenon. This information was used in the design process of the TMD (Tuned Mass Damping) system used on the structures to suppress the vibrations. The behaviour of the real structures was then experimentally verified in order to check their structural parameters (frequencies, damping and modal shapes) with respect to the expected ones calculated using a FEM model, and to verify the proper behaviour of the designed TMD system. The data coming from the modal identification of the structures permitted also a final tuning of the TMDs. The two arches were then monitored for several months to observe their dynamic behaviour under different wind conditions. A wide database was gathered, collecting the strongest and most frequent environmental occurrences in the field. The accelerations registered during the considered period did not reach dangerous levels for the structures, in agreement with the expected results obtained from wind tunnel tests.